Commitment in an organizational context: a SET-theoretic approach that provides management tools. Issue 1 (5th July 2021) - Curado, Carla; Jerónimo, Helena Mateus; Henriques, Paulo Lopes; Tavares, Marta
Abstract : Purpose: Grounded on the social exchange theory (SET), this paper aims to analyze the different networks of conditions that lead to the presence and absence of total commitment, in its affective, continuance and normative dimensions. Six conditions – competencies development, empowerment, work-family conflict, trust, transformational leadership and seniority – are studied to explore and explain the exchanges and reciprocity relationships between organizations and employees. Design/methodology/approach: Using a sample of 546 employees from Portuguese large companies, the study uses the fuzzy-set qualitative comparative analysis (fsQCA) to explore how causal conditions jointly link to the outcome of organizational commitment. Findings: The results show more causal configurations leading to the most favorable dimensions of commitment (affective, normative and the absence of continuance commitment), which is a positive sign for organizations. Employees' seniority stands out in all types of commitment, reflecting the affective and emotional themes in Portuguese culture. Originality/value: This study makes an original contribution to the literature on organizational commitment by showing the alternative complementarity of the conditions in the context of the SET, only possible through fsQCA. It also provides inputs for practitioners who can adopt strategies and measures to develop the paths that lead to successful outcomes (presence of commitment) and avoid those that lead to undesired ones (absence of commitment).